The Relationship between the Ratio of Neutrophil and Lymphocyte in Preeclampsia Patients - Ayuni, Intan Nabilla; Yeni, Cut Meurah; Husnah, Husnah; Sakdiah, Sakdiah (Asian Journal of Healthcare Analytics, 2025)
Preeclampsia is a hypertensive disorder with elevated blood pressure and proteinuria after 20 weeks of gestation, often involving an exaggerated inflammatory response. This study examined the relationship between the neutrophil-to-lymphocyte ratio (RNL) and preeclampsia. A retrospective analytic study with a cross-sectional approach analyzed medical records of 106 inpatients at Zainoel Abidin Hospital Banda Aceh from January to December 2020. Most patients were aged 20-35 years (64.2%), college-educated (38.8%), housewives (68.9%), and multiparas (62%). RNL analysis showed 8.6% normal and 91.4% abnormal in severe preeclampsia cases. The Spearman correlation test showed p=0.367 (p>0.05), indicating no significant relationship between RNL and preeclampsia. The mean RNL was 6.5267 in preeclampsia and 8.3106 in severe cases, both exceeding the normal cut-off of 4.8. There was no relationship between RNL and preeclampsia, but the mean RNL values were above normal.